Characterizing local metallic bonding variation induced by external perturbation. Issue 4 (14th January 2020) - Wang, Hongwei; Fuller, Jon; Chen, Peng; Morozov, Sergey I.; An, Qi
Abstract : The reduced density gradient analyses on metallic bonding indicate that FCC metals can become more flexible/stronger with the electron/hole injection. Abstract : The subtle variation of metallic bonding, induced by external influence, plays an essential role in determining physical, mechanical, and chemical properties of metals. However, it is extremely difficult to describe this variation because of the delocalization nature of metallic bonding. Here, we utilize the reduced density gradient and topological analysis of electron density to capture the local metallic bonding variations (LMBV) caused by lattice distortion and carrier injection in many face-centered cubic (fcc) metals. We find that the LMBV determines the traits of fcc metals such as strength, malleability, and ductility. Moreover, the fcc metals can become more flexible/stronger with the electron/hole injection, providing an important guidance to tune metals for desired mechanical properties.